Implementación de un sistema contable para el almacén de repuestos master truck´s Cummis Diesel Ubicada En El Cantón Latacunga, Provincia De Cotopaxi, período del 1º de julio al 31 diciembre de 2012 - Bautista Bautista, Ibelia Nataly (2014)
The research in the “Master truck's Cummis Diesel” stock car parts located in Latacunga city, Cotopaxi Province helped to identify the entity didn’t have an adequate accounting management to be able to know the turnover and the profitability percentage that it is achieved in a given period. Also it was important to get specific information through techniques as survey, interview and observation. They were conducted to the management, administrative staff and customers. It was necessary to show an analysis with the collected information and it helped to establish that the stock need to implement an accounting system, so that it will permit to get a reliable information to take decisions, therefore it is indispensable to encourage to the stock’s owners the importance that accounting has as financial analysis so, they improve the stock’s development.